Failure mechanism and support system of roofs in advance areas affected by mining under the condition of soft rock stratum - Li, Jun; Lian, Xiaoyong; Li, Chen; Wu, Zheng; Wang, Jun (Frontiers in Earth Science, 2022)
The advance area affected by mining (AAAM) of the Lijiahao coal mine is influenced by the superposition of the side and advance abutment pressure, and the roadway roof is considerably damaged. General support technology and equipment cannot economically and effectively maintain the stability of the roadway roof of AAAM. Through field detection, theoretical analysis, and numerical simulation, this study analyzes the structure of the surrounding rock, the evolution characteristics of the regional stress field, the distribution of the surrounding rock plastic zone, and the influencing factors of the plastic zone in the AAAM of the Lijiahao mine. The results show the following. (1) The direct roof and floor of the roadway is coal, siltstone, and sandy mudstone, which has low strength and can be easily broken. (2) The Max and Min principal stresses in the AAAM reach 2.3 and 1.5 times of in-situ stress, respectively, and the ratio of the two is 2–8, which causes the shape of the plastic zone of the surrounding rock to turn into a butterfly shape. (3) The principal stress direction of AAAM deflects at a large angle, which causes the deepest failure direction of the surrounding rock to rotate to the roof and floor of the roadway. Accordingly, herein, a self-moving foldable support system is proposed to support the AAAM of the Lijiahao coal mine. The system will not support the roof repeatedly and is suitable for soft rock stratum. In addition, it can also adapt to the heave of roadway floor and avoid dumping. The mechanized operation of the system makes the roof support in AAAM more efficient and safer.